2009
DOI: 10.1530/rep-09-0190
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian follicle development in Booroola sheep exhibiting impaired bone morphogenetic protein signalling pathway

Abstract: The role of bone morphogenetic proteins (BMPs) in the regulation of ovarian function has been extensively investigated but the mechanism of regulation is not well understood. The aim of this study was to investigate the effect of mutation in the BMP receptor in Booroola sheep on the number of primordial follicles and rate of follicle recruitment in comparison with that in normal merino sheep in vivo. Whole sheep ovaries at the time of birth, 1.5 and 5 years old were collected and processed for the follicle qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 35 publications
8
19
0
Order By: Relevance
“…We have supported these in vitro studies using in vivo models namely the Booroola sheep (Ruoss et al 2009) and mice passively immunised against BMP4 (Tanwar et al 2008), both models are characterised by attenuated action of the BMP signalling system, similar to that initially described in Bmp4 lacZneo haplo-insufficient mice (Lawson et al 1999). Our recent report has confirmed that the attenuation of the BMP signalling system by a natural point mutation of BMPRIB in Booroola sheep reduces the rate of primordial follicle recruitment, while increasing primary follicle survival (Ruoss et al 2009). However, it has not yet been determined whether such an effect of BMPs is a sheep species and/or a Booroola strain specific phenomenon or can be applied to other species and different experimental conditions.…”
Section: Introductionsupporting
confidence: 68%
See 4 more Smart Citations
“…We have supported these in vitro studies using in vivo models namely the Booroola sheep (Ruoss et al 2009) and mice passively immunised against BMP4 (Tanwar et al 2008), both models are characterised by attenuated action of the BMP signalling system, similar to that initially described in Bmp4 lacZneo haplo-insufficient mice (Lawson et al 1999). Our recent report has confirmed that the attenuation of the BMP signalling system by a natural point mutation of BMPRIB in Booroola sheep reduces the rate of primordial follicle recruitment, while increasing primary follicle survival (Ruoss et al 2009). However, it has not yet been determined whether such an effect of BMPs is a sheep species and/or a Booroola strain specific phenomenon or can be applied to other species and different experimental conditions.…”
Section: Introductionsupporting
confidence: 68%
“…The sections were consecutively labelled, mounted on a glass slide and stained with haematoxylin and eosin for further stereological studies. For this purpose, the stages of follicle development were classified according to previous reports (Myers et al 2004, Ruoss et al 2009). In brief, primordial follicles appeared as a primary oocyte surrounded by a single layer of squamous granulosa cells (Fig.…”
Section: Ovaries and Histologymentioning
confidence: 99%
See 3 more Smart Citations